A COMPARISON OF THERMOCAUTERY AND CRYOSURGERY AS DISBUDDING METHODS IN BUFFALO CALVES - Mahida, H H; Tank , P H; Dhami , M A; Vala , K B; Vagh , A A (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Fourteen clinically healthy buffalo calves of either sex, with age varying between 01 to 04 weeks were selected for comparative study of the two methods of disbudding viz., thermocautery (Group - I; 6) and cryosurgery (Group - II; 8). The buffalo calves between the age group of 01 to 04 weeks were found suitable for both the methods of disbudding. Cryoguard protected horn bud were cryofrozen to -40°C. The cryosurgical disbudding did not lead to any open wound at the site and so also the cryofrozen horn buds remained at the site which later sloughed off progressively providing a natural biological covering to the underlying granulating bed till the completion of the healing. The cryosurgical disbudding was found to be cost-effective, practically surgeon convenient and clinically feasible as well as advantageous and so also less stressful to the subject as compared to the thermocautery disbudding in buffalo calves.